ANALISIS BIAYA PANEN DAN PASCA PANEN CENGKEH DI DESA KAWENG KECAMATAN KAKAS KABUPATEN MINAHASA - Rain ., Panekenan; Caroline B. D. Pakasi; Lyndon R. J. Pangemanan (Sam Ratulangi University, 2018)
This study aims to analyze the cost of harvest and post-harvest cloves. This research was conducted in Kaweng Village Kakas Subdistrict of Minahasa Regency and lasted from July until September 2016. The research method used in this research is survey method. Data collection method in this research is by using primary data and secondary data. Sampling method is by using simple random sampling method. The data analysis used is the data collected tabulated by using cost analysis. The results of this study was that each harvest activity costs vary, it is issued in accordance with the needs of farmers to support harvest and post-harvest activities for 2-3 months during the 1st harvest and post harvest period. The largest average is at the cost of picking of Rp.222.352.500. Each production was influenced by variable costs and fixed costs at one time of production at the price of the cloves present at harvest, where the variable cost amounts to Rp.360.243.500 and fixed costs Rp.1.866.000 in production amount of 8.677 kg with an average price of Rp.106.050 per kg.*jnkd*.